Transformation of Plasmid pET Endo-1,4-Î²-xilanase from E. coli TOP10 to E. coli BL21 - Santoso, Agung Budi; Kurniawati, Eka Yuni; Ratnadewi, Anak Agung Istri (UNEJ e-Proceeding, 2014)
In this research we successfully transmited Plasmid pET- Endo from E.coli TOP10 to E.coli BL21. Plasmid pET Endo is recombinant plasmid base on pET-30a(+)Â inserted with gene of endo-1,4-Î²-xilanase isolated from bacillus subtilis sp which is originally living in termite abdomen. First step is isolation of plasmid pET-Endo from E.coli TOP10 with alkaline lyses. Denaturation and renaturation of DNA occurred then separated with centrifugation. Plasmid pET-Endo is smaller than Chromosome DNA. Agarose gel electrophoresis confirmed that Plasmid pET-Endo has isolated. Electrogram of pET-Endo show the band in 6022 bp compare to empty plasmid pET-30a(+) 5422 bp. E.Coli BL21 got pretreatment withÂ CaCl2 solution to make cell competent for transformation. Isolated pET-Endo inserted to E.coli BL21 with heat shock method. Resistance test with antibiotic has done to know the result of transformation. E.coli BL21 contained plasmid pET-Endo will survive in kanamycin agar media. Colony of E.coli BL21 then cultured in liquid media and examinee itâs growth phase. IPTG as gene inducer given after 2,5 hour of inoculation. Crude enzyme tested for xilanase activity and well proved. Isolation of plasmid pET-Endo then running in Agarose gel electrophoresis also confirm good result of transformation.